A ubiquitin-related gene signature for predicting prognosis and constructing molecular subtypes in osteosarcoma - Wei, Nan; Chao-yang, Gong; Wen-ming, Zhou; Ze-yuan, Lei; Yong-qiang, Shi; Shun-bai, Zhang; Kai, Zhang; Yan-chao, Ma; Hai-hong, Zhang (Frontiers in Pharmacology, 2022)
Background: Ubiquitination is medicated by three classes of enzymes and has been proved to involve in multiple cancer biological process. Moreover, dysregulation of ubiquitination has received a growing body of attention in osteosarcoma (OS) tumorigenesis and treatment. Therefore, our study aimed to identify a ubiquitin related genes signature for predicting prognosis, immune landscape, and constructing OS molecular subtypes. Methods: Therapeutically Applicable Research to Generate Effective Treatments (TARGET) was regard as the training set through univariate Cox regression, Lasso Cox regression and multivariate Cox regression. The GSE21257 and GSE39055 served as the validation set to verify the predictive value of the signature. CIBERSORT was performed to show immune infiltration and the immune microenvironment. The NMF algorithm was used to construct OS molecular subtypes. Results: In this study, we developed a ubiquitin related genes signature including seven genes (UBE2L3, CORO6, DCAF8, DNAI1, FBXL5, UHRF2, WDR53) and the genes signature had a good performance in predicting prognosis for OS patients (AUC values at 1/3/5 year were 0.957, 0.890, and 0.919). Multivariate Cox regression indicated that risk score model and prognosis stage were also independent prognostic prediction factors. Moreover, analyses of immune cells and immune-related functions showed significant difference in different risk score groups and the three clusters. The drug sensitivity suggested that IC50 of proteasome inhibitor (MG-132) was notable significance between the risk score groups (p<0.05). Through NMF algorithm, we obtained the three clusters and cluster 3 showed better survival outcomes.The expression of ubiquitin related genes (CORO6, UBE2L3, FBXL5, DNAI1 DCAF8) showed an obvious significance in normal and osteosarcoma tissues. Conclusion: We developed a novel ubiquitin related genes signature which showed better predictive prognostic ability for OS and provided additional information on chemotherapy and immunotherapy. The OS molecular subtypes would also give the useful guide for individualized therapy.